ESTIMATION OF RUNOFF FOR GOIZHA-DABASHAN WATERSHED WITH AID OF REMOTE SENSING TECHNIQUES (Journal of Engineering, 2011)
Estimation of runoff volume and peak runoff is necessary for designing and operating the dams. One of the accepted models for estimating the runoff is HEC-1 model. Two methods were used in this study to estimate the runoff in Goizha-Dabashan watershed, 2.02 km2, Rational method and Soil Conservation Service curve number method (SCS-CN). Satellite image from Landsat-7 (ETM+) was used to develop land use and soil type maps. Watershed was delineated from DEM (http: //www.emrl.byu. edu/gsdu) with resolution 10 m with aid of WMS 7.1 software. Runoff coefficient was calculated by inverse the Rational equation. Manual calibration was performed until the Nash-Sutcliffe coefficient gives the best results. Results showed that the runoff coefficient is 0.05 and the curve number value for conditions II and III are 75 and 80.5 respectively after calibration. Also, curve number method is better than Rational method for estimating the peak runoff discharge.